2015
DOI: 10.1371/journal.pone.0141243
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reflection and the Diligent Worker: An Experimental Study of Millennials

Abstract: Recent studies have shown that despite crucially needing the creative talent of millennials (people born after 1980) organizations have been reluctant to hire young workers because of their supposed lack of diligence. We propose to help resolve this dilemma by studying the determinants of task performance and shirking behaviors of millennials in a laboratory work environment. We find that cognitive ability is a good predictor of task performance in line with previous literature. In contrast with previous resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 57 publications
(61 reference statements)
1
30
0
1
Order By: Relevance
“…For instance, Insler, Compton, and Schmitt [51] found a correlation coefficient of 0.31 (n = 364) between the CRT and GPA, and Toplak et al [24] found a correlation coefficient of 0.23 (n = 160) between the CRT and the self-reported GPA. However, Corgnet, Hernán Gonzalez, and Mateo [52] did not find a relationship between the CRT and GPA (r = 0.04; n = 264). The second issue refers to the relationship between CR and job performance.…”
Section: Cognitive Reflection Job Performance Academic Performancementioning
confidence: 80%
“…For instance, Insler, Compton, and Schmitt [51] found a correlation coefficient of 0.31 (n = 364) between the CRT and GPA, and Toplak et al [24] found a correlation coefficient of 0.23 (n = 160) between the CRT and the self-reported GPA. However, Corgnet, Hernán Gonzalez, and Mateo [52] did not find a relationship between the CRT and GPA (r = 0.04; n = 264). The second issue refers to the relationship between CR and job performance.…”
Section: Cognitive Reflection Job Performance Academic Performancementioning
confidence: 80%
“…One essential implication of our study is that thinking too much may hamper important aspects of divergent creative thinking. This result is of primary relevance to hiring managers who may want to rely on cognitive reflection as the main criterion to recruit diligent (Corgnet et al, 2015b) and creative millennials. Our findings suggest that the cognitive tests used to recruit workers have to be adapted to the nature of the job offered.…”
Section: Discussionmentioning
confidence: 92%
“…Standard measures of cognitive ability have been found to correlate positively with task performance (Schmidt et al, 1986; Murphy, 1989) and negatively with counterproductive work behaviors such as theft or absenteeism (Dilchert et al, 2007). Moreover, the results of a recent study suggest that these effects may be mediated by individuals' cognitive styles (Corgnet et al, 2015b). In particular, Corgnet et al (2015b) find that millennials characterized by a more reflective style (as measured by the Cognitive Reflection Test; Frederick, 2005) are more diligent, displaying higher levels of task performance and lower levels of counterproductive work behaviors 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects in the first group are observed by another subject, those from the second group observe another subject and subjects in the third group work 1 Furthermore, a number of field experiments study the effect of related personal attributes such as self-control on real-life outcomes (see for instance Buechel et al (2014) who link self-control to academic success and Kaur et al (2010) who link it to success at work). Also, a number of laboratory experiments investigate the determinants of shirking in real-effort tasks (see for instance Corgnet et al (2015) on diligence in summing up numbers or Bucciol et al (2013) on the ability to withstand temptation in a counting task) and the effects of being observed by group members (see for example Charness et al (2007) and Andreoni & Bernheim (2009)).…”
Section: Introductionmentioning
confidence: 99%